Open Sesame: a new generation journal - Bhui, Kamaldeep (BJPsych Open, 2015)
SUMMARY: The Royal College of Psychiatrists welcomes you to its newest peer-reviewed research journal, British Journal of Psychiatry Open (BJPsych Open), which has been created to maximise the College’s efforts to publish and disseminate the most exciting and progressive research in psychiatry and allied disciplines. BJPsych Open will maintain the same high quality standards established by the British Journal of Psychiatry (BJPsych). As an online journal without print restrictions, BJPsych Open will be able to publish many more excellent articles and article types not currently accommodated within BJPsych. The breadth of BJPsych Open is outlined in ‘What we publish’ and its strength is realised in our first issue, ‘Powerful papers’. As editors, we welcome both your submissions and comments as our new generation journal grows. DECLARATION OF INTEREST: None. COPYRIGHT AND USAGE: © The Royal College of Psychiatrists 2015. This is an open access article distributed under the terms of the Creative Commons Non-Commercial, No Derivatives (CC BY-NC-ND) licence.